1998
DOI: 10.1183/09031936.98.12040913
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-beta1 in sarcoidosis

Abstract: Transforming growth factor-beta (TGF-beta) is a cytokine that promotes extracellular matrix accumulation and inhibits matrix degradation. Although the natural course of sarcoidosis is usually favourable, granuloma healing in the lung may result in pulmonary fibrosis and respiratory impairment in some patients. In this study TGF-beta1 was evaluated in bronchoalveolar lavage (BAL) fluid and culture supernatants of alveolar macrophages (AM) from 73 patients with biopsy-proven sarcoidosis. Disease activity was def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 26 publications
2
47
0
Order By: Relevance
“…Increased levels of TGFβ have been reported in the BAL fluid of patients with sarcoidosis, 13 but a recent study also reported increased TGFβ levels in the BAL fluid of patients with altered lung function. 14 The role of TGFβ therefore still needs to be defined. Enhanced secretion of IL-10 has been observed from alveolar macrophages but not from BAL fluid cells of patients with sarcoidosis.…”
mentioning
confidence: 99%
“…Increased levels of TGFβ have been reported in the BAL fluid of patients with sarcoidosis, 13 but a recent study also reported increased TGFβ levels in the BAL fluid of patients with altered lung function. 14 The role of TGFβ therefore still needs to be defined. Enhanced secretion of IL-10 has been observed from alveolar macrophages but not from BAL fluid cells of patients with sarcoidosis.…”
mentioning
confidence: 99%
“…TGF-b1 is a pleiotropic cytokine with effects on cell growth and differentiation, extracellular matrix formation and fibrosis, and immunomodulation. For example, elevated levels of active TGF-b1 were seen in the BAL of fibrotic sarcoidosis patients compared with normal control subjects (48). Several functional single nucleotide polymorphisms within the TGF-b1 gene have been identified, including C2509T, codon 10 (T 1 29C), and codon 25 (G 1 74C) (49).…”
Section: Discussionmentioning
confidence: 99%
“…[86,87] The variant allele C of -509T/C and C of codon 10 are associated with higher TGF-β1 protein levels in the serum and the codon 10 variant is associated with increased mRNA levels in PBMC. [88,89] TGF-β1 levels in the BAL and alveolar macrophage supernatant are higher in patients with active sarcoidosis and especially in those with pulmonary function changes, [90] there was also a positive correlation with BAL lymphocytosis. [90] No association was found between sarcoidosis and 2 polymorphisms (codon 10, T869C) in the TGF-β1 gene in a Japanese sarcoidosis cohort and no relationship with Scadding chest x-ray stage was found either.…”
Section: Tgf-βmentioning
confidence: 92%
“…[88,89] TGF-β1 levels in the BAL and alveolar macrophage supernatant are higher in patients with active sarcoidosis and especially in those with pulmonary function changes, [90] there was also a positive correlation with BAL lymphocytosis. [90] No association was found between sarcoidosis and 2 polymorphisms (codon 10, T869C) in the TGF-β1 gene in a Japanese sarcoidosis cohort and no relationship with Scadding chest x-ray stage was found either. [91] Codon 10 was also not associated with sarcoidosis in a German cohort [92].…”
Section: Tgf-βmentioning
confidence: 92%